Recovery of Bacillus cereus cyclodextrin glycosyltransferase and recycling of phase components in an aqueous two-phase system using thermo-separating polymer - Ng, H.S.; Tan, C.P.; Mokhtar, M.N.; Ibrahim, S.; Ariff, A.; Ooi, C.W.; Ling, T.C. (2012)
An aqueous two-phase system (ATPS) composed of thermo-separating polymer and salt was deployed in this study for the recovery of Bacillus cereus cyclodextrin glycosyltransferase (CGTase) and recycling of phase components simultaneously. CGTase was recovered using ATPS over two successive extractions and the recycled phase-forming polymers were utilized for subsequent extraction. ATPSs constructed by different molecular weight of the thermo-separating copolymers ethylene oxide-propylene oxide (EOPO) and potassium phosphate salt were tested for their effects on partitioning of the enzyme CGTase into top phase. Besides, the effects of phase composition, tie-line length (TLL), crude load, volume ratio (V R) and pH of the ATPS on the partitioning behavior of CGTase were studied to achieve optimum purification condition. Copolymer recovery was measured in each successive ATPS. The optimum purification of enzyme CGTase was obtained in the EOPO 3900/phosphate ATPS comprising TLL of 41.2% (w/w), V R of 1.25, and crude load of 20% (w/w) and pH of 7.0. CGTase from B. cereus was successfully purified by the ATPS up to 13.1-fold with a yield of 87% and the EOPO 3900 could be recovered up to 80% after the first enzyme extraction from ATPS. Â© 2012 Elsevier B.V. All rights reserved.